Process for Making Self-Locking Pavements from Madagascar River Sand and Plastic Waste - Rakotomamonjy L.; Rakotomamonjy P.; Razafindramanga A. W.; Rakotondramanana V. Henintsoa; Bakoarisoa Andrianina Cynthia; Ramahandry Jean Elidon; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina B. (Budapest International Research in Exact Sciences (BirEx) Journal, 2023)
This work focuses on the manufacture of self-locking pavement from a mixture of river sand and waste from the recovery of plastic film packaging of the cookie and confectionery JB and wastes plastic bags collected at the university campus of Vontovorona. The sand is sifted to select the appropriate granulometry, which is higher than 0.5 mm on the one hand, and that is lower than 0.5 mm on the other hand. The sand with a grain size greater than 0.5 mm is mixed with the plastic waste in accordance with the manufacturing dosage. Different proportions of sand/plastic waste ranging from 40/60 to 70/30 have been prepared. The absorption rate increases with the proportion of sand added. This is true for both types of plastic waste. This absorption rate is increased for the pavers with plastic bag waste as binders. For the latter, the lowest rate of 2.2 is close to the highest rate of 2.1 for paving stones with JB plastic packaging waste as binders. The obtained pavers have a good mechanical strength higher than 12,000 daN.